National Health Insurance: An Implementation Framework of Nizam Al Mulk’s Thoughts - Lusianti, Dina; Nasrullah, Muhammad; Yusoff, Rushami; Setyawan, Rai (International Journal of Islamic Business and Economics (IJIBEC), 2024)
Maintaining public welfare is a key challenge in contemporary Islamic economies. This study examines how Nizam al-Mulk’s political-economic thought—particularly taxation, hisbah, fiscal oversight, and savings—provides a framework for national health insurance. Employing a library research approach, the study utilizes bibliometric tools such as Publish or Perish, VOSviewer, Connected Papers, and Research Rabbit to analyze scholarly discourse and assess the relevance of Nizam al-Mulk’s governance model. The findings suggest that Nizam al-Mulk’s governance principles—justice, transparency, and institutional integrity—align with Indonesia’s National Health Insurance (JKN). Key implications include the role of the National Social Security Council, cigarette tax revenue allocation, and the conceptualization of health insurance as long-term savings. This study shows that Islamic political-economic heritage can guide modern policies, provide ethical legitimacy and promote social solidarity in equitable healthcare. Furthermore, it underscores the necessity of inclusive public policies that integrate religious ethical values with welfare-state objectives. This research contributes to bridging classical Islamic governance models with modern socio-economic systems and advocates for comparative studies across Muslim-majority contexts.